Outcome of revision hip arthroplasty in patients younger than 55 years: an analysis of 1,037 revisions in the Dutch Arthroplasty Register - Kuijpers, Martijn F L; Hannink, Gerjon; Steenbergen, Liza N Van; Schreurs , B Willem (Acta Orthopaedica, 2020)
Background and purpose — The increasing use of hip arthroplasties in young patients will inevitably lead to more revision procedures at younger ages, especially as the outcome of their primary procedures is inferior compared with older patients. However, data on the outcome of revision hip arthroplasty in young patients are limited. We determined the failure rates of revised hip prostheses performed in patients under 55 years using Dutch Arthroplasty Register (LROI) data. Patients and methods — All 1,037 revised hip arthroplasty procedures in patients under 55 years at the moment of revision registered in the LROI during the years 2007–2018 were included. Kaplan–Meier survival analyses were used to calculate failure rates of revised hip arthroplasties with endpoint re-revision for any reason. Competing risk analyses were used to determine the probability of re-revision for the endpoints infection, dislocation, acetabular and femoral loosening, while other reasons for revisions and death were considered as competing risks. Results — Mean follow-up of revision procedures was 3.9 years (0.1–12). 214 re-revisions were registered. The most common reason for the index revision was dislocation (20%); the most common reason for re-revision was infection (35%). The 5-year failure rate of revised hip prostheses was 22% (95% CI 19–25), and the 10-year failure rate was 28% (CI 24–33). The 10-year cumulative failure rates of index revisions with endpoint re-revision for infection was 7.8% (CI 6.1–9.7), acetabular loosening 7.0% (CI 4.1–11), dislocation 3.8% (CI 2.6–5.2), and femoral loosening 2.7% (CI 1.6–4.1). The 10-year implant failure rate of index revisions for infection was 45% (CI 37–55) with endpoint re-revision for any reason. Interpretation — Failure rate of revised hip prostheses in patients under 55 years is worrisome, especially regarding index revisions due to infection. This information facilitates realistic expectations for these young patients at the time of primary THA.